A technical note on the derivation of Zakat Effectiveness Index (ZEIN) - Abdullah, Naziruddin; Mohd Yusop, Mohd Mahyudi; Awang, Che Omar (International Islamic University Malaysia, 2012)
Effectiveness of policies is very much dependent upon the quality of the measures used to guide the formulation of those policies. Thus, methodological and practical issues surrounding poverty and inequality indices are of paramount importance in poverty alleviation efforts. This paper attempts to propose a Zakat Effectiveness Index (ZEIN) to address some of those issues. The strength of the index is as follows: 1) it can be used to verify and compare how effective is the expenditures on poverty alleviation by the government as represented by the amount of zakat distributed to the eligible zakat recipients; 2) it is flexible enough to incorporate different sub-groups analysis such as types of employment, sectors or ethnic groups; and, 3) unlike other indices that use the GNP and GDP as denominator, ZEIN introduces zakat recipients as the denominator to improve the effectiveness of the poverty index. Lumped together, ZEIN measures more directly the shortfall ofzakat distribution vis-à-vis the total expenditure on basic needs requiredfor the poor to sustain a decent minimum livelihood. Finally, we assertthat ZEIN is potentially a very useful tool to measure the performance of all Muslim countries’ provision 76 International Journal of Economics, Management and Accounting 20, no. 1 (2012) of minimum basic needs through zakat to further promote the achievement of the maqasid al-shari’ah.